The impact of religious affiliation on the unmet need for family planning of women in the Philippines - Gan, Stephanie Natalie C.; Tee, Clarice Kimberley M.; Epetia, Christina (Quezon City School of Economics, University of the Philippines Diliman, 2020)
Background: Religions prescribe moral codes that limit the choices individuals make for themselves, even in the aspect of reproductive health decisions. In the Philippines, approximately 96 percent of the population identify to have a religious affiliation and thus are highly influenced by religious doctrine. This secular state has constantly struggled with the influence and power that religious institutions like the Catholic Church hold, even within politics. In order for the Philippines to meet their international pledges United Nations (UN) with respect to their 2030 Sustainable Development Goals (SDGs) and be successful in meeting targets set by the Philippine Development Plan 2017-2022, population control and reproductive health for women must be improved. To do this, it is important to identify the barriers that keep women from having full control over their decisions related to their reproductive health. This critical assessment of the Unmet Need for Family Planning (FP) can help policy-makers understand the crucial elements in drive this indicator, so that the government may better monitor and evaluate the Philippine population and health programs.

Methods: The Demographic Health Survey (DHS) data for more than 25,000 women from over 31,000 households aged 15- 49 are analyzed in this study. Through a Multivariate Logistic Regression model, the probability of having an Unmet Need for (FP), based on varying independent variables, like one’s religious affiliation, is determined.

Results: Only Islamic and Other Christian affiliates are found to have significant coefficients and hence significant average marginal effects. The researchers discovered that Muslim women are 9.77 percent less likely to have an unmet need than Catholic women, while Other Christian women are 2.81 percent more likely to have an Unmet Need for (FP) than the base group. Furthermore, being a part of any other religious minority group in the country, or not having a religious affiliation at all, is deemed to be insignificant factors in determining an individual’s need for FP. Out of all the other relevant control variables tested in this study, a woman’s age, level of educational attainment, exposure to family planning messages on television, and region of residence are deemed to be significant in determining the likelihood of having an Unmet Need for (FP) relative to their respective base groups.

Conclusion: The dominance of religion in the Philippines means that religious influence in reproductive health behaviors of women is inevitable. Thus, the approach that the government takes in order to address the unmet needs of women must change. Beyond the usual recommendations for improving implementation and increasing awareness on FP, the government must work with Faith-Based Organizations (FBOs) and other religious institutions to decrease the negative connotation associated with contraception among the religious Filipinos, who are the majority of the population.
Thesis (BS Economics) - - University of the Philippines Diliman
Includes bibliographical references and appendix.
Keywords: Family planning; Family planning -- Religious aspects